Do mineral supplements decrease the efficacy of quinolone antibiotics?. Issue 4 (April 2017) - Walker, William R.; Tyler, Carl
Abstract : Bottom line : Mineral supplements and antacids containing the metal cations of iron, zinc, calcium, and aluminum appear to significantly lessen the bioavailability of quinolones, although the clinical significance on efficacy is not known (SOR: C, based on pharmacokinetic data).